Image Processing: Algorithms and Systems X; And Parallel Processing for Imaging Applications II 2012
DOI: 10.1117/12.910605
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of different image-based biofeedback models for improving cycling performances

Abstract: "Sport practice can take advantage from the quantitative assessment of task execution, which is strictly connected to the implementation of optimized training procedures. To this aim, it is interesting to explore the effectiveness of biofeedback training techniques. This implies a complete chain for information extraction containing instrumented devices, processing algorithms and graphical user interfaces (GUIs) to extract valuable information (i.e. kinematics, dynamics, and electrophysiology) to be presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…In this way, the subjects were helped to effectively orient the forces along the pedaling cycle, receiving real time information about which sector of the cycle they had to improve to reach an optimal pedaling technique (Bibbo et al, 2012). An entirely filled circle thus corresponds to IE = 1.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, the subjects were helped to effectively orient the forces along the pedaling cycle, receiving real time information about which sector of the cycle they had to improve to reach an optimal pedaling technique (Bibbo et al, 2012). An entirely filled circle thus corresponds to IE = 1.…”
Section: Methodsmentioning
confidence: 99%
“…On this assumption, the position of each element in the sagittal plane, being their lengths known, can be reconstructed using 2 of the relative angles values θC, θP, θ1, θ2, θ3. The angles θC and θP, together with the pedal forces Fn and Ft, along the perpendicular and parallel axis to the pedal load plane, were directly measured on a cycling simulator [14,30], already validated in recent works for monitoring cycling activity in real time [31]. An inverse dynamics model provided muscular moments for each joint.…”
Section: Biomechanical Modelmentioning
confidence: 99%
“…Different representations are used to provide information to the athlete, and some studies in the literature focus on the use of visualization techniques (Aris et al, 2005). The aim of letting cyclists learn to pull up on the pedal and thus increase Eff Mech , has driven some authors to present visual feedback to the riders in rather different ways (Sanderson, 1987; Mornieux et al, 2010; Bibbo et al, 2012). The above-mentioned studies reported a significant variation of the pedaling gesture with the use of visual feedback confirming the hypothesis that, independently of the particular rendering scheme, the use of biofeedback allows riders to improve Eff Mech .…”
Section: Factors Related To Cycling Performancementioning
confidence: 99%